Biology and life cycle of rice moth Corcyra cephalonica, Lepidoptera, Pyralidae (Ricos Biology, 2025)
The rice moth, Corcyra cephalonica, is a significant pest of stored food commodities, causing both quantitative and qualitative damage to grains through its larvae, which feed on cereals, pulses, oilseeds, spices, and dried fruits. The species exhibits complete metamorphosis with a life cycle including an egg incubation period of 5 days, a larval period of 23-25 days, a pupal period of 10 days, and an adult lifespan of approximately 1 week. The larvae damage grains by feeding within silken webs, often converting stored grain into a webbed mass, rendering it unfit for human consumption (Bhandari et al., 2009). Efforts to rear C. cephalonica on efficient food media resulted in the production of robust moths and eggs, which are crucial for rearing egg parasitoids (Pathak et al., 2010).Recent studies have focused on alternative pest control methods, given the growing concerns over chemical pesticide use. Fenoxycarb, a juvenile hormone analog, has shown promising results in controlling C. cephalonica. Six different concentrations of fenoxycarb (0.025%, 0.05%, 0.1%, 0.25%, 0.5%, and 1.0%) were tested on last instar larvae, with concentration-dependent mortality observed. Higher concentrations (0.5% and 1.0%) resulted in larval mortality before reaching the adult stage, while lower concentrations (0.025% and 0.05%) led to developmental delays, morphological abnormalities, and reduced fecundity in females. Moreover, exposure of normal eggs to fenoxycarb prevented hatching in 37.2%-57.2% of eggs, indicating its gonadotropic action (Begum and Qamar, 2016).In an effort to optimize rearing conditions for C. cephalonica, nine dietary formulations were tested, incorporating various combinations of rice, wheat, sorghum, and groundnut. The diet comprising sorghum and groundnut (T6) yielded the best results, with the shortest larval (30.33 days) and pupal (7 days) periods, the lowest total developmental period (47.33 days), and the highest rates of adult emergence (82%) and fecundity (312.33). This diet also resulted in the longest female longevity (9.67 days) and highest male longevity (8.33 days), contributing significantly to mass rearing efforts for the large-scale production of C. cephalonica (Arun Kumar et al., 2018).This research offers valuable insights into the biology, pest control, and rearing optimization of C. cephalonica, highlighting the potential of fenoxycarb as an effective management tool and providing suitable diets for large-scale production.